If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7m + 21 + -5(m + -1) = 8m + -1(4m + -3) + -9m + 2 Reorder the terms: -7m + 21 + -5(-1 + m) = 8m + -1(4m + -3) + -9m + 2 -7m + 21 + (-1 * -5 + m * -5) = 8m + -1(4m + -3) + -9m + 2 -7m + 21 + (5 + -5m) = 8m + -1(4m + -3) + -9m + 2 Reorder the terms: 21 + 5 + -7m + -5m = 8m + -1(4m + -3) + -9m + 2 Combine like terms: 21 + 5 = 26 26 + -7m + -5m = 8m + -1(4m + -3) + -9m + 2 Combine like terms: -7m + -5m = -12m 26 + -12m = 8m + -1(4m + -3) + -9m + 2 Reorder the terms: 26 + -12m = 8m + -1(-3 + 4m) + -9m + 2 26 + -12m = 8m + (-3 * -1 + 4m * -1) + -9m + 2 26 + -12m = 8m + (3 + -4m) + -9m + 2 Reorder the terms: 26 + -12m = 3 + 2 + 8m + -4m + -9m Combine like terms: 3 + 2 = 5 26 + -12m = 5 + 8m + -4m + -9m Combine like terms: 8m + -4m = 4m 26 + -12m = 5 + 4m + -9m Combine like terms: 4m + -9m = -5m 26 + -12m = 5 + -5m Solving 26 + -12m = 5 + -5m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '5m' to each side of the equation. 26 + -12m + 5m = 5 + -5m + 5m Combine like terms: -12m + 5m = -7m 26 + -7m = 5 + -5m + 5m Combine like terms: -5m + 5m = 0 26 + -7m = 5 + 0 26 + -7m = 5 Add '-26' to each side of the equation. 26 + -26 + -7m = 5 + -26 Combine like terms: 26 + -26 = 0 0 + -7m = 5 + -26 -7m = 5 + -26 Combine like terms: 5 + -26 = -21 -7m = -21 Divide each side by '-7'. m = 3 Simplifying m = 3
| 7/x+2=4/2x-3 | | x^2+x-3.25=0 | | 3.6+y=1 | | 4/5k-5=-7+2/3k | | x-2-6x=4 | | -[8z-(11z+9)]=9+(2z+3) | | 4m^3-10m^2= | | -2p-6(3-2p)=6(p-3)-16 | | 5x+10=-20fory | | 3x(x-2)+5(x-2)=0 | | 38x-38=38x-38 | | -8(4b+4)+(33b-9)=0 | | 5x+6(x-11)=5(x-12) | | -2=t-3s | | 62+(6x)+(6x+6)=180 | | 16s^2+72s+18=0 | | 12(-82x+26)=84(2x+62) | | 5/3x=56 | | x+5/3=56 | | 4c^2-36c=0 | | 9(3x+6)+(x+2)=11 | | 2n(8n+1)=0 | | 9x+90+y=180 | | x(-5x+2)=24 | | -3u-w=u+7w | | 4x+8+5x-7=180 | | 12+6x=42 | | 6=t+7s | | 6(t-3)+6t=4(3t+5)-12 | | 5x-9x+8=-2+6 | | -2+3x=12 | | -6z-6=-12z+12 |